Surface-modified wollastonite fiber as well as preparation method and application thereof

By surface modification of wollastonite fibers, the cross-linking reaction of aluminum silicate sol and polystyrene-polyacrylic acid copolymer is used to enhance the bonding strength of wollastonite fibers and recycled concrete, solving the problem of poor permeability and crack resistance of recycled concrete, and achieving higher mechanical properties and durability.

CN120349109APending Publication Date: 2025-07-22深圳市锦昊辉实业发展有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510531170.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

When recycled concrete uses waste concrete aggregate, there are problems with poor permeability and crack resistance, which is mainly due to the intimate interface bond caused by the surface and internal microcracks of the aggregate, which affects the overall performance.

Method used

After mixing wollastonite fibers with aluminum silicate sol, calcining and coupling reaction, and then crosslinking with polystyrene-polyacrylic acid copolymer, surface-modified wollastonite fibers are formed to enhance their bond strength and interface bonding with recycled concrete.

Benefits of technology

It improves the mechanical properties, permeability and crack resistance of recycled concrete, enhances the interface bonding strength, improves the combination of recycled aggregate and fresh slurry, reduces porosity, and improves the durability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005376678410000161
    Figure BDA0005376678410000161
Patent Text Reader

Abstract

The invention discloses a surface-modified wollastonite fiber as well as a preparation method and application thereof, and relates to the technical field of wollastonite fibers. The preparation method of the surface modified wollastonite fiber comprises the following steps: mixing wollastonite fiber and aluminum silicate sol, and calcining to obtain aluminum silicate modified wollastonite fiber; coupling the aluminum silicate modified wollastonite fibers by using an amino silane coupling agent to obtain amino modified wollastonite fibers; and crosslinking the amino-modified wollastonite fiber and a polystyrene-polyacrylic acid copolymer to obtain the surface-modified wollastonite fiber. The surface of the wollastonite fiber is coated with the aluminum silicate, so that the interaction between the wollastonite fiber and the recycled concrete is enhanced, the bonding strength between the wollastonite fiber and the recycled concrete can be enhanced, a hydrophobic flexible interface layer is formed through the polystyrene-polyacrylic acid copolymer, stress can be relieved, and more concrete can participate in hydration. The technical scheme provided by the invention can be used for improving the crack resistance and impermeability of the recycled concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wollastonite fibers, and particularly relates to a surface-modified wollastonite fiber, a preparation method thereof, and an application thereof. Background Art

[0002] Recycled concrete refers to new concrete prepared by crushing, cleaning, and grading waste concrete blocks, mixing them in a certain proportion and gradation, partially or completely replacing natural aggregates such as sand and gravel, and then adding cement, water, etc.

[0003] Compared with natural aggregates, a large amount of old cement mortar adheres to the surface of recycled aggregates processed from waste concrete. When used in the preparation of new concrete, it is easy to generate a multi-interface structure and a high interfacial water-cement ratio. Moreover, the recycled aggregates need to undergo mechanical operations such as crushing, which easily causes a large number of microcracks on the surface and inside of the recycled aggregates. As a result, when preparing concrete with recycled aggregates, the workability of the mixture becomes significantly worse, and the mechanical properties and durability after hardening are also significantly reduced. A large number of microcracks generated on the surface and inside of the recycled aggregates will also cause microcracks in the recycled concrete system, and the hardened slurry bound to the surface of the recycled aggregates will affect the bonding tightness between the recycled aggregates and the concrete slurry, further reducing the impermeability and crack resistance of the recycled concrete. These problems limit the resource utilization of waste concrete.

[0004] Therefore, it is urgent in this field to develop a recycled concrete with good impermeability and crack resistance. Summary of the Invention

[0005] The main object of the present invention is to propose a surface-modified wollastonite fiber, a preparation method thereof, and an application thereof, aiming to solve the problems of poor impermeability and poor crack resistance existing in recycled concrete.

[0006] To achieve the above object, the present invention proposes a preparation method for a surface-modified wollastonite fiber, comprising the following steps:

[0007] S1. Mix wollastonite fibers and aluminosilicate sol to obtain wollastonite fibers coated with aluminosilicate sol;

[0008] S2. Calcinate the wollastonite fibers coated with aluminosilicate sol to obtain aluminosilicate-modified wollastonite fibers;

[0009] S3. Mix the aluminosilicate-modified wollastonite fibers and an amino-silane coupling agent to carry out a coupling reaction to obtain amino-modified wollastonite fibers;

[0010] S4. Mix the amino-modified wollastonite fibers and a polystyrene-polyacrylic acid copolymer to carry out a crosslinking reaction to obtain surface-modified wollastonite fibers.

[0011] In one embodiment, before step S1, it further includes:

[0012] Mix silicate ester, aluminum salt and aqueous ethanol solution to obtain a mixed solution, and then mix the mixed solution with an acid solution to carry out a hydrolysis and polycondensation reaction to obtain an aluminosilicate sol;

[0013] Wherein, the molar ratio of the silicate ester to the aluminum salt is (2-3):1.

[0014] In one embodiment, in step S1:

[0015] The mass ratio of the wollastonite fiber to the aluminosilicate sol is 100:(3-6); and / or,

[0016] The method of mixing the wollastonite fiber and the aluminosilicate sol includes: stirring the wollastonite fiber and the aluminosilicate sol at 60-80°C for 6-12 h.

[0017] In one embodiment, in step S2:

[0018] The calcination temperature is 400-600°C; and / or,

[0019] The calcination time is 2-4 h.

[0020] In one embodiment, in step S3:

[0021] The amino silane coupling agent includes 3-aminopropyltriethoxysilane; and / or,

[0022] The mass ratio of the aluminosilicate-modified wollastonite fiber to the amino silane coupling agent is 100:(1-3); and / or,

[0023] The temperature of the coupling reaction is 55-65°C; and / or,

[0024] The time of the coupling reaction is 5-7 h; and / or,

[0025] The pH value of the coupling reaction is 4-5.

[0026] In one embodiment, in step S4:

[0027] The mass ratio of the amino-modified wollastonite fiber to the polystyrene-polyacrylic acid copolymer is 1:(0.5-1.2); and / or,

[0028] The temperature of the crosslinking reaction is 20-30°C; and / or,

[0029] The time of the crosslinking reaction is 12-24 h; and / or,

[0030] The pH value of the crosslinking reaction is 7-8.

[0031] The present invention provides a surface-modified wollastonite fiber, and the surface-modified wollastonite fiber is obtained according to the preparation method of the surface-modified wollastonite fiber.

[0032] The present invention provides an application of the surface-modified wollastonite fiber in the preparation of recycled aggregate concrete.

[0033] In one embodiment, the preparation of the recycled aggregate concrete includes the following steps:

[0034] Provide a cementitious material, modified wollastonite fiber, water reducer, suspending agent, water, fine aggregate and recycled coarse aggregate;

[0035] Mix and stir the cementitious material and the modified wollastonite fiber to obtain a cementitious mixture; mix and stir the water reducer, the suspending agent and water to obtain an admixture solution;

[0036] Mix and stir the cementitious mixture, the admixture solution, the fine aggregate and the recycled coarse aggregate to obtain recycled aggregate concrete;

[0037] Wherein, the modified wollastonite includes the surface-modified wollastonite fiber.

[0038] In one embodiment, the mass ratio of the cementitious material, the modified wollastonite fiber, the water reducer, the suspending agent, water, the fine aggregate and the recycled coarse aggregate is 100:(0.1-0.3):(0.8-1.5):(0.1-0.3):(40-60):(120-150):(180-220); and / or,

[0039] The cementitious material includes cement and silica fume, and the mass ratio of the cement and the silica fume is (9-10):(1-1.8); and / or,

[0040] The fine aggregate includes natural sand, and the particle size of the natural sand is 0.075-4.0 mm; and / or,

[0041] The recycled coarse aggregate includes recycled crushed stone, and the particle size of the recycled crushed stone is 5-20 mm.

[0042] In the technical solution of the present invention, wollastonite fibers are modified with aluminum silicate sol. Through the condensation reaction between the silanol groups of the aluminum silicate sol and the silanol groups of the wollastonite fibers, a polymer network structure is formed, thereby coating the surface of the wollastonite fibers with aluminum silicate. This not only increases the roughness of the wollastonite fibers, which is beneficial to enhancing the bonding strength between the wollastonite fibers and recycled concrete, but also improves the compatibility between the wollastonite fibers and recycled concrete, enabling the wollastonite fibers and the concrete matrix to form a strong interfacial bond through ionic bonds or covalent bonds. Among them, the silicate ions in the aluminum silicate react with calcium hydroxide in the concrete to generate the cement hydration product C-S-H gel, which helps to enhance the interfacial adhesion. The aluminum ions in the aluminum silicate react with calcium hydroxide in the cement to generate calcium aluminate hydrate, which helps to enhance the compactness. Moreover, the introduction of aluminum ions can also improve the corrosion resistance and high-temperature stability of the coating layer. Secondly, after being treated with an amino silane coupling agent, the surface of the modified wollastonite fibers is provided with amino groups. Finally, the amino-modified wollastonite fibers are treated with a polystyrene-polyacrylic acid copolymer. The reaction occurs through the carboxyl groups in the polyacrylic acid reacting with the amino groups of the silane coupling agent and the hydroxyl groups on the surface of the aluminum silicate, thereby connecting the polystyrene-polyacrylic acid copolymer with the aluminum silicate-modified wollastonite fibers. By introducing a polymer, a flexible interfacial layer is covered on the surface of the wollastonite, which helps to relieve stress concentration, improve the crack resistance and toughness of the recycled concrete. At the same time, the introduced polystyrene segments form a hydrophobic layer, which helps to improve the hydrophobic performance of the wollastonite fibers, enabling more concrete mixing water to participate in hydration, generating more hydration products, reducing the porosity of the recycled aggregate concrete, and improving the compactness of the recycled aggregate concrete, thereby improving the mechanical properties, impermeability and crack resistance of the recycled aggregate concrete. Detailed implementation manners

[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0044] It should be noted that if there are directional indications (such as up, down, left, right, front, back...) involved in the embodiments of the present invention, the directional indications are only used to explain the relative positional relationship and movement conditions between components in a specific posture. If the specific posture changes, the directional indications will also change accordingly.

[0045] In addition, if the embodiments of the present invention involve descriptions such as "first", "second", etc., the descriptions of "first", "second", etc. are only for descriptive purposes and should not be construed as indicating or implying their relative importance or implicitly indicating the quantity of the indicated technical features. Thus, the features defined with "first" and "second" may explicitly or implicitly include at least one such feature. In addition, if "and / or" or "and / or" appears throughout the text, its meaning includes three parallel scenarios. Taking "A and / or B" as an example, it includes Scenario A, or Scenario B, or the scenario where both A and B are satisfied simultaneously. In addition, the technical solutions between various embodiments can be combined with each other, but it must be based on the ability of those of ordinary skill in the art to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0046] During the mechanical operation in the process of producing recycled aggregate from waste concrete, many microcracks invisible to the naked eye will be generated inside and on the surface of the recycled aggregate. These microcracks will continue to expand during the concrete forming and service processes, negatively affecting the pore structure of the concrete, increasing the porosity of the concrete, and further reducing the impermeability and crack resistance of the concrete. On the other hand, more or less hardened slurry that has already formed in the waste concrete is bonded to the surface of the recycled aggregate, making it impossible for the recycled aggregate to closely bond with the fresh slurry in the fresh concrete system, further increasing the porosity of the internal structure of the concrete and further reducing the impermeability and crack resistance of the concrete. These problems have greatly restricted the resource utilization of waste concrete. Therefore, it is urgent in this field to develop a recycled concrete with good impermeability and crack resistance.

[0047] Wollastonite is a naturally occurring calcium silicate mineral with a needle-like or fibrous crystal structure. Wollastonite fibers have been widely used in many fields such as rubber, coatings, plastics, and environmental protection due to their excellent mechanical properties, thermal stability, and chemical stability, and relatively low cost. Although there have been some applications using wollastonite fibers to improve the compressive strength and crack resistance of concrete, during the mixing process of concrete, due to the water absorption of wollastonite fibers to a certain extent, the water content of the concrete itself will be reduced, which will instead reduce the early strength of the concrete, resulting in the concrete matrix becoming less dense, thus having a negative impact on the overall compressive strength. Therefore, the dosage of wollastonite fibers in actual applications is usually small, resulting in a very limited strengthening effect of wollastonite fibers. In addition, the specific surface area of wollastonite fibers is high. Not only is it easy to agglomerate and the addition process needs to be controlled, but also the compatibility between wollastonite fibers and recycled concrete is poor, which greatly limits its effectiveness.

[0048] Based on the above background, the present invention proposes a preparation method for surface-modified wollastonite fibers, including the following steps:

[0049] S1. Mix wollastonite fibers and aluminum silicate sol to obtain wollastonite fibers coated with aluminum silicate sol;

[0050] S2. Calcinate the wollastonite fibers coated with aluminum silicate sol to obtain wollastonite fibers modified with aluminum silicate;

[0051] S3. Mix the wollastonite fibers modified with aluminum silicate and an amino-silane coupling agent, and carry out a coupling reaction to obtain wollastonite fibers modified with amino groups;

[0052] S4. Mix the wollastonite fibers modified with amino groups and a polystyrene-polyacrylic acid copolymer, and carry out a crosslinking reaction to obtain wollastonite fibers with surface modification.

[0053] The technical solution of the present invention provides a preparation method of surface-modified wollastonite fibers. In this preparation method, wollastonite fibers are first wrapped with an aluminosilicate sol to obtain aluminosilicate-modified wollastonite fibers. Subsequently, the aluminosilicate-modified wollastonite fibers are subjected to amination modification with a silane coupling agent. Finally, a polystyrene-polyacrylic acid copolymer is connected to the surface of the aluminosilicate-modified wollastonite fibers through a chemical bonding method. In the technical solution of the present invention, the wollastonite fibers are modified with an aluminosilicate sol. Through the condensation reaction between the silanol groups (Si-OH) of the aluminosilicate sol and the silanol groups (Si-OH) of the wollastonite fibers, a polymer network structure is formed, thereby coating the wollastonite fibers with aluminosilicate. This not only increases the roughness of the wollastonite fibers, which is beneficial to enhancing the bonding strength between the wollastonite fibers and recycled concrete, but also improves the compatibility between the wollastonite fibers and recycled concrete, enabling the wollastonite fibers to form a strong interfacial bond with the concrete matrix through ionic bonds or covalent bonds. Among them, the silicate ions in the aluminosilicate react with calcium hydroxide in the concrete to generate the cement hydration product C-S-H gel, which helps to enhance the interfacial bond. The aluminum ions in the aluminosilicate react with calcium hydroxide in the cement to generate calcium aluminate hydrate (C-A-H), which helps to enhance the compactness. Moreover, the introduction of aluminum ions can also improve the corrosion resistance and high-temperature stability of the coating layer. Secondly, after treatment with an amino silane coupling agent, the surface of the modified wollastonite fibers is provided with amino groups. Finally, the amino-modified wollastonite fibers are treated with a polystyrene-polyacrylic acid copolymer. The reaction occurs through the carboxyl groups in the polyacrylic acid reacting with the amino groups of the silane coupling agent and the hydroxyl groups on the surface of the aluminosilicate, thereby connecting the polystyrene-polyacrylic acid copolymer to the aluminosilicate-modified wollastonite fibers. By introducing a polymer, a flexible interfacial layer is formed on the surface of the wollastonite, which helps to relieve stress concentration, improve the crack resistance and toughness of the recycled concrete. At the same time, the introduced polystyrene segments form a hydrophobic layer, which helps to improve the hydrophobic performance of the wollastonite fibers, enabling more concrete mixing water to participate in hydration, generating more hydration products, reducing the porosity of the recycled aggregate concrete, and improving the compactness of the recycled aggregate concrete, thereby improving the mechanical properties, impermeability and crack resistance of the recycled aggregate concrete.

[0054] In an embodiment of the present invention, before step S1, it further includes:

[0055] S10. Mix a silicate ester, an aluminum salt and an ethanol aqueous solution to obtain a mixed solution. Subsequently, mix the mixed solution and an acid solution and carry out a hydrolysis and polycondensation reaction to obtain an aluminosilicate sol;

[0056] Wherein, the molar ratio of the silicate ester to the aluminum salt is (2-3):1.

[0057] The silicate ester undergoes a hydrolysis reaction in water to form silanol (Si-OH) groups. The aluminum salt also undergoes hydrolysis in water to obtain hydrolysis products containing hydroxyl groups. The silanol (Si-OH) groups and the hydrolysis products of the aluminum salt can undergo dehydration polycondensation reactions to finally form a complex three-dimensional network structure, namely aluminosilicate sol. Considering the bonding strength between wollastonite fibers and recycled concrete and controlling costs at the same time, the technical solution of the present invention sets the molar ratio of the silicate ester to the aluminum salt to (2-3):1. Controlling within the above range can also reduce the adverse effects caused by excessive aluminum ions (such as inhibiting hydration).

[0058] In an embodiment of the present invention, in step S10, the silicate ester includes at least one of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate, and butyl silicate. In an embodiment of the present invention, ethyl orthosilicate is selected to prepare aluminosilicate sol.

[0059] In an embodiment of the present invention, in step S10, the aluminum salt includes at least one of aluminum nitrate and aluminum sulfate. Considering that the chloride ions in aluminum chloride are not conducive to the impermeability of concrete, aluminum nitrate or aluminum sulfate is selected as the aluminum salt. In an embodiment of the present invention, lithium nitrate is selected to prepare aluminosilicate sol.

[0060] In an embodiment of the present invention, in step S10, in the ethanol aqueous solution, the volume ratio of ethanol to water is 2:1. Ethanol is used to dissolve ethyl orthosilicate, and water is used to dissolve the aluminum salt and improve the hydrolysis environment.

[0061] In an embodiment of the present invention, in step S10, the acid solution includes nitric acid; when the hydrolysis reaction is carried out, the pH value of the mixed solution is 3-5. By adding nitric acid to control the pH during the hydrolysis polycondensation reaction within 3-5, the efficiency of the hydrolysis polycondensation reaction is high in this range.

[0062] In an embodiment of the present invention, in step S10, the temperature of the hydrolysis polycondensation reaction is 20-30°C, and the time of the hydrolysis polycondensation reaction is 2-4 h. Aluminosilicate sol can be prepared at room temperature. After mixing the silicate ester, aluminum salt, and ethanol aqueous solution, stir for 2-4 h until a transparent sol, namely aluminosilicate sol, is formed.

[0063] In an embodiment of the present invention, in step S1, the diameter of the wollastonite fiber is 12-20 μm. Since the particle size distribution of recycled aggregates is relatively complex, selecting finer fibers helps to fill the pores between aggregates and reduce stress concentration. Moreover, finer fibers usually have higher strength and toughness, playing a reinforcing role in the composite material to prevent fracture or collapse caused by external forces.

[0064] In an embodiment of the present invention, in step S1, the length of the wollastonite fiber is 15 - 20 mm. When the fiber length is relatively long, the wollastonite fiber can span wide cracks between recycled aggregates, thereby enhancing the toughness of recycled concrete; when the fiber length is relatively short, it helps to fill the pores between aggregates. The technical solution of the present invention selects wollastonite fibers with a length of 15 - 20 mm, which helps to obtain recycled concrete with balanced crack resistance and impermeability performance.

[0065] In an embodiment of the present invention, in step S1, the mass ratio of the wollastonite fiber to the aluminosilicate sol is 100:(3 - 6). Controlling the mass ratio of the wollastonite fiber to the aluminosilicate sol to 100:(3 - 6) can improve the anchoring effect of the fiber in the weak interface area and avoid the problem of fiber embrittlement caused by an overly thick coating layer. Within this range, the mass ratio of the wollastonite fiber to the aluminosilicate sol can be 100:3, 100:4, 100:5, or 100:6.

[0066] In an embodiment of the present invention, in step S1, the method of mixing the wollastonite fiber and the aluminosilicate sol includes: stirring the wollastonite fiber and the aluminosilicate sol at 60 - 80 °C for 6 - 12 h.

[0067] Constant temperature stirring of the wollastonite fiber and the aluminosilicate sol at 60 - 80 °C can promote the polycondensation of the sol into a film on the material surface.

[0068] In an embodiment of the present invention, in step S2, the calcination temperature is 400 - 600 °C. Within this range, the calcination temperature can be 400 °C, 450 °C, 500 °C, 550 °C, or 600 °C.

[0069] In an embodiment of the present invention, in step S2, the calcination time is 2 - 4 h. Within this range, the calcination time can be 2 h, 3 h, or 4 h. Calcination treatment promotes the formation of an Al - O - Si network and forms an amorphous or microcrystalline aluminosilicate coating layer on the surface of wollastonite. In an embodiment of the present invention, the wollastonite fiber coated with the aluminosilicate sol is selected to be calcined at 550 °C for 2 h.

[0070] In an embodiment of the present invention, step S3 includes:

[0071] Mixing the aluminosilicate - modified wollastonite fiber, the amino - silane coupling agent, and the ethanol aqueous solution, and performing a coupling reaction to obtain an amino - modified wollastonite fiber.

[0072] Mixing a silicate ester and an aluminum salt to obtain a mixed solution, and then mixing the mixed solution and an acid solution to perform a hydrolysis and polycondensation reaction to obtain an aluminosilicate sol.

[0073] In an embodiment of the present invention, in step S3, in the aqueous ethanol solution, the volume ratio of ethanol to water is 4:1.

[0074] In an embodiment of the present invention, in step S3, the amino-silane coupling agent includes 3-aminopropyltriethoxysilane. By introducing amino groups through the amino-silane coupling agent, the polyacrylic acid in the polystyrene-polyacrylic acid copolymer can be connected not only through the hydroxyl groups on the aluminosilicate, but also through the amino groups, which helps to improve the bonding strength between the polystyrene-polyacrylic acid copolymer and the aluminosilicate coating layer on the surface of wollastonite fibers.

[0075] In an embodiment of the present invention, in step S3, the mass ratio of the aluminosilicate-modified wollastonite fibers to the amino-silane coupling agent is 100:(1-3). Controlling the dosage of the amino-silane coupling agent within the above range is beneficial to reducing side reactions. In an embodiment of the present invention, the mass ratio of the aluminosilicate-modified wollastonite fibers to the amino-silane coupling agent is set to 100:1.5.

[0076] In an embodiment of the present invention, in step S3, the temperature of the coupling reaction is 55-65°C. Within this range, the temperature of the coupling reaction can be 50°C, 60°C, or 65°C. In an embodiment of the present invention, the temperature of the coupling reaction is set to 60°C.

[0077] In an embodiment of the present invention, in step S3, the time of the coupling reaction is 5-7 h. Within this range, the time of the coupling reaction can be 5 h, 6 h, or 7 h. In an embodiment of the present invention, the time of the coupling reaction is set to 6 h.

[0078] In an embodiment of the present invention, in step S3, the pH value of the coupling reaction is 4-5. At this pH, the hydrolysis effect of the silane coupling agent is better. Acetic acid can be used to adjust the pH.

[0079] In an embodiment of the present invention, step S4 includes:

[0080] Activating the polystyrene-polyacrylic acid copolymer (PS-PAA) to obtain the activated polystyrene-polyacrylic acid copolymer, mixing the activated polystyrene-polyacrylic acid copolymer with the amino-modified wollastonite fibers, and performing a crosslinking reaction to obtain the surface-modified wollastonite fibers.

[0081] In order to enhance the activity of the groups in the polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are used to activate the carboxyl groups of PS-PAA. After activation, the activated PS-PAA can be fixed on the aluminosilicate on the surface of wollastonite through amide bonds.

[0082] In an embodiment of the present invention, in step S4, in the polystyrene-polyacrylic acid copolymer, the molecular weight of the polystyrene is 15,000 to 30,000, the molecular weight of the polyacrylic acid is 2,000 to 8,000, and the molar ratio of the polystyrene to the polyacrylic acid is (3 to 5):1. Polystyrene and polyacrylic acid are common chemical products, which is beneficial to cost control. Polystyrene is a hydrophobic chain segment. If the molecular weight is too high, the long chain segment will hinder the dispersion of wollastonite fibers in concrete; if the molecular weight is too low, the provided hydrophobicity is limited. Polyacrylic acid provides carboxyl groups for anchoring connection with aluminum silicate. If the molecular weight is too high, the long chain segment will hinder the dispersion of wollastonite fibers in concrete; if the molecular weight is too low, the carboxyl density decreases, reducing the chemical bonding with the aluminum silicate coating layer. In an embodiment of the present invention, a polystyrene-polyacrylic acid graft copolymer is used, wherein the molecular weight of the polystyrene is 20,000, the molecular weight of the polyacrylic acid is controlled at 5,000, and the molar ratio of the polystyrene to the polyacrylic acid is 4:1. With such a setting, the hydrophobic chain segment dominates, providing sufficient hydrophobicity, and can also enable wollastonite fibers to have a good dispersion effect in recycled concrete, while enhancing the chemical bonding between the polystyrene-polyacrylic acid copolymer and the aluminum silicate coating layer.

[0083] In an embodiment of the present invention, in step S4, the mass ratio of the amino-modified wollastonite fibers to the polystyrene-polyacrylic acid copolymer is 1:(0.5 to 1.2). Within this range, the mass ratio of the amino-modified wollastonite fibers to the polystyrene-polyacrylic acid copolymer can be 1:0.5, 1:0.7, 1:0.9, 1:1.0, or 1:1.2. If the addition amount of the copolymer is too large, it may cause the wollastonite fibers to be overly wrapped, hindering the bonding between the aluminum silicate coating layer and the concrete, and instead weakening the strength of the recycled concrete. Controlling the usage amounts of the amino-modified wollastonite fibers and the polystyrene-polyacrylic acid copolymer within the above range can improve the interfacial transition zone between the aggregate and the cement paste in the recycled concrete and increase its bonding strength.

[0084] In an embodiment of the present invention, in step S4, the temperature of the crosslinking reaction is 20 to 30 °C. Controlling the temperature of the crosslinking reaction within the above range can achieve a uniform crosslinking effect, which is beneficial to reducing side reactions.

[0085] In an embodiment of the present invention, in step S4, the time of the crosslinking reaction is 12 to 24 h. When the crosslinking reaction is controlled within the above range, the reaction can be more complete and the crosslinking density can be increased.

[0086] In an embodiment of the present invention, in step S4, the pH value of the crosslinking reaction is 7 to 8. Controlling the pH within this range helps the carboxyl groups to react with the amino groups.

[0087] The present invention provides a surface-modified wollastonite fiber, and the surface-modified wollastonite fiber is prepared according to the preparation method of the surface-modified wollastonite fiber.

[0088] The present invention provides an application of the surface-modified wollastonite fiber in the preparation of recycled aggregate concrete.

[0089] Recycled aggregate concrete has defects such as high porosity, weak interface, and strong water absorption, which limit the resource utilization of waste concrete. After applying the surface-modified wollastonite fiber prepared by the present invention to recycled aggregate concrete, the hydrophobic chain segments of the wollastonite fiber reduce the absorption of mixing water in the concrete system, so that more mixing water can participate in hydration, increase the amount of hydration products in the recycled aggregate concrete, enhance the compactness of the recycled aggregate concrete, and further improve the mechanical properties, impermeability and crack resistance of the concrete; in addition, compared with the unmodified wollastonite fiber, the surface-modified wollastonite fiber can be evenly dispersed in the concrete system, which is beneficial to uniformly improving the bonding strength between the recycled aggregate and the fresh slurry; furthermore, since the surface of the prepared surface-modified wollastonite fiber is coated with aluminum silicate, this increases the roughness of the wollastonite fiber, can enhance the bonding strength between the wollastonite fiber and the recycled concrete, and the silicate ions in the aluminum silicate can react with calcium hydroxide in the recycled concrete to form the cement hydration product C-S-H gel, which helps to enhance the interfacial bonding. The aluminum ions in the aluminum silicate react with calcium hydroxide in the cement to form calcium aluminate hydrate (C-A-H), which helps to enhance the compactness, and further improve the mechanical properties, impermeability and crack resistance of the concrete. Moreover, the aluminum ions can also improve the corrosion resistance and high-temperature stability of the coating layer, and further improve the durability of the recycled concrete.

[0090] In an embodiment of the present invention, the preparation of the recycled aggregate concrete includes the following steps:

[0091] Provide a cementitious material, modified wollastonite fiber, water reducer, suspending agent, water, fine aggregate and recycled coarse aggregate;

[0092] Mix and stir the cementitious material and the modified wollastonite fiber to obtain a cementitious material mixture; mix and stir the water reducer, suspending agent and water to obtain an admixture solution;

[0093] Mix and stir the cementitious material mixture, the admixture solution, the fine aggregate and the recycled coarse aggregate to obtain recycled aggregate concrete;

[0094] Wherein, the modified wollastonite includes the surface-modified wollastonite fiber.

[0095] In the preparation scheme of the present invention, first, the gelling material and the modified wollastonite fiber are mixed and stirred to make the modified wollastonite fiber evenly dispersed in the gelling material, and then the rubber mixture, the admixture solution, the fine aggregate and the recycled aggregate are mixed. Through the above technical scheme, recycled concrete with good impermeability and crack resistance can be prepared.

[0096] In the embodiment of the present invention, the mass ratio of the gelling material, the modified wollastonite fiber, the water reducing agent, the suspending agent, water, the fine aggregate and the recycled coarse aggregate is 100:(0.1 - 0.3):(0.8 - 1.5):(0.1 - 0.3):(40 - 60):(120 - 150):(180 - 220). Considering the characteristics of high porosity, high water absorption and low strength of the recycled aggregate and the strengthening effect of the surface-modified wollastonite fiber, the mass ratio of the gelling material, the modified wollastonite fiber, the water reducing agent, the suspending agent, water, the fine aggregate and the recycled coarse aggregate is set within the above range, so that the prepared recycled aggregate concrete has good impermeability and crack resistance and enhanced durability.

[0097] In the embodiment of the present invention, the gelling material includes cement and silica fume, and the mass ratio of the cement and the silica fume is (9 - 10):(1 - 1.8). The gelling material is selected to be compounded with cement and silica fume, which can reduce the heat of hydration and improve the long-term strength. Among them, due to the small particle size of silica fume and its micro-aggregate filling effect, it can play a role in filling the small pores inside the cement-based composite material, making the structure of the prepared recycled aggregate concrete denser. And silica fume can combine with calcium hydroxide in the concrete to form the cement hydration product C-S-H gel, further improving the compactness of the recycled aggregate concrete, and improving the impermeability and crack resistance of the recycled aggregate concrete. The technical scheme of the present invention selects silica fume with a particle size of 0.1 - 0.3 μm.

[0098] In the embodiment of the present invention, the water reducing agent includes a polycarboxylic acid type water reducing agent.

[0099] In the embodiment of the present invention, the suspending agent includes hydroxypropyl methylcellulose.

[0100] Considering that the dosage of the surface-modified wollastonite fiber is relatively large in the technical scheme of the present invention, the water reducing agent and the suspending agent are added to compensate for the fluidity loss caused by the wollastonite fiber, so as to improve the workability of the concrete mixture, and further improve the mechanical properties of the concrete.

[0101] In the embodiment of the present invention, the fine aggregate includes natural sand, and the particle size of the natural sand is 0.05 - 4.0 mm.

[0102] In an embodiment of the present invention, the recycled coarse aggregate includes recycled crushed stones, and the particle size of the recycled crushed stones is 5 - 20 mm. The recycled coarse aggregate is graded to reduce the porosity. In one embodiment of the present invention, recycled crushed stones with a particle size of 5 - 10 mm and recycled crushed stones with a particle size of 10 - 20 mm are selected, and the mass ratio of the recycled crushed stones with a particle size of 5 - 10 mm to the recycled crushed stones with a particle size of 10 - 20 mm is set to 4:6.

[0103] The technical solution of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0104] Example 1

[0105] A preparation method of surface-modified wollastonite fibers includes the following steps:

[0106] (1) Mix 416.6 g of tetraethyl orthosilicate, 375.1 g of aluminum nitrate nonahydrate, and 450 mL of an ethanol aqueous solution (the volume ratio of ethanol to water is 2:1) to obtain a mixed solution. Subsequently, adjust the pH value of the mixed solution to 3 - 5 with nitric acid, and carry out a hydrolysis and polycondensation reaction at room temperature for 4 h to obtain a silica-alumina sol.

[0107] (2) Mix 100 g of wollastonite fibers (with a diameter of 12 - 20 μm and a length of 15 - 20 mm) and 5 g of the silica-alumina sol, stir at a constant temperature of 70 °C for 12 h, then carry out centrifugal separation, wash with water 3 times to remove the unreacted sol, and dry at 80 °C for 12 h to obtain wollastonite fibers coated with the silica-alumina sol.

[0108] (3) Calcinate the wollastonite fibers coated with the silica-alumina sol at 550 °C for 2 h to obtain silica-alumina-modified wollastonite fibers.

[0109] (4) Mix 100 g of the silica-alumina-modified wollastonite fibers, 1.5 g of 3-aminopropyltriethoxysilane, and 500 mL of an ethanol aqueous solution (the volume ratio of ethanol to water is 4:1), carry out a coupling reaction at 60 °C and pH 4 for 6 h. After the reaction, carry out centrifugation, then wash with deionized water and ethanol 3 times in sequence, and dry in vacuum at 60 °C for 12 h to obtain amino-modified wollastonite fibers; adjust the pH with acetic acid.

[0110] (5) Dissolve 5 g of polystyrene-polyacrylic acid copolymer (PS-PAA) in a carboxyl-activated buffer solution with pH 5.5 (50 mM MES buffer solution, pH 6.0, and the mass concentration of PS-PAA in the MES buffer solution is 5 mg / mL). Add 10 mg of EDC and 4 mg of NHS, stir at room temperature for 2 h, and purify it in a desalting column to remove the excess EDC and NHS, obtaining the activated polystyrene-polyacrylic acid copolymer. Disperse 5 g of amino-modified wollastonite fibers in PBS phosphate buffer solution with pH 7.4 (the mass concentration of wollastonite fibers is 5 mg / mL), then add 2.5 g of the activated polystyrene-polyacrylic acid copolymer, and carry out a cross-linking reaction at room temperature. After reacting for 24 h, perform centrifugal separation (10000 rpm, 10 min), then wash it with deionized water and ethanol three times in sequence to remove the unbonded copolymer, and then place it in a vacuum dryer at 40 °C for 12 h to obtain the surface-modified wollastonite fibers.

[0111] Example 2

[0112] Compared with Example 1, the difference lies in that the mass of tetraethyl orthosilicate in step (1) is 625.0 g.

[0113] Example 3

[0114] Compared with Example 1, the difference lies in that the mass ratio of wollastonite fibers to aluminosilicate sol in step (2) is 100:3.

[0115] Example 4

[0116] Compared with Example 1, the difference lies in that the mass ratio of wollastonite fibers to aluminosilicate sol in step (2) is 100:6.

[0117] Example 5

[0118] Compared with Example 1, the difference lies in that the mass ratio of the amino-modified wollastonite fibers to the polystyrene-polyacrylic acid copolymer in step (5) is 1:1.0.

[0119] Example 6

[0120] Compared with Example 1, the difference lies in that the mass ratio of the amino-modified wollastonite fibers to the polystyrene-polyacrylic acid copolymer in step (5) is 1:1.2.

[0121] Example 7

[0122] Application of a surface-modified wollastonite fiber in the preparation of recycled aggregate concrete, and the preparation of the recycled concrete includes the following steps:

[0123] (1) Provide raw materials: 90 kg of cement, 10 kg of silica fume, 0.1 kg of the modified wollastonite fiber of Example 1, 0.8 kg of water reducer, 0.1 kg of suspending agent, 40 kg of water, 120 kg of natural sand, 72 kg of 5 - 10 mm recycled coarse aggregate, 108 kg of 10 - 20 mm recycled coarse aggregate;

[0124] (2) Mix and stir the cement, silica fume and modified wollastonite fiber to obtain a binder mixture; mix and stir the water reducer, suspending agent and water to obtain an admixture solution;

[0125] (3) Mix and stir the binder mixture, the admixture solution, the fine aggregate and the recycled coarse aggregate to obtain recycled aggregate concrete.

[0126] Example 8

[0127] Compared with Example 7, the difference lies in the raw material dosages: 100 kg of cement, 18 kg of silica fume, 0.3 kg of the modified wollastonite fiber of Example 1, 1.5 kg of water reducer, 0.3 kg of suspending agent, 60 kg of water, 150 kg of natural sand, 88 kg of 5 - 10 mm recycled coarse aggregate, 132 kg of 10 - 20 mm recycled coarse aggregate.

[0128] Example 9

[0129] Compared with Example 7, the difference lies in the raw material dosages: 95 kg of cement, 15 kg of silica fume, 0.2 kg of the modified wollastonite fiber of Example 1, 1.0 kg of water reducer, 0.2 kg of suspending agent, 50 kg of water, 130 kg of natural sand, 80 kg of 5 - 10 m recycled coarse aggregate, 120 kg of 10 - 20 mm recycled coarse aggregate.

[0130] Example 10

[0131] Compared with Example 7, the difference is that the modified wollastonite fiber is the surface - modified wollastonite fiber prepared in Example 2.

[0132] Example 11

[0133] Compared with Example 7, the difference is that the modified wollastonite fiber is the surface - modified wollastonite fiber prepared in Example 3.

[0134] Example 12

[0135] Compared with Example 7, the difference is that the modified wollastonite fiber is the surface - modified wollastonite fiber prepared in Example 4.

[0136] Example 13

[0137] Compared with Example 7, the difference lies in that the modified wollastonite fiber is the surface-modified wollastonite fiber prepared in Example 5.

[0138] Example 14

[0139] Compared with Example 7, the difference lies in that the modified wollastonite fiber is the surface-modified wollastonite fiber prepared in Example 6.

[0140] Comparative Example 1:

[0141] Compared with Example 1, the difference lies in that unmodified wollastonite fiber is used instead of the wollastonite fiber modified with aluminum silicate, that is, steps (1) to (3) are omitted.

[0142] Comparative Example 2:

[0143] Compared with Example 1, the difference lies in that polystyrene-polyacrylic acid copolymer is not used, that is, steps (4) and (5) are omitted.

[0144] Comparative Example 3:

[0145] Compared with Example 1, the difference lies in that polystyrene of equal mass is used instead of polystyrene-polyacrylic acid copolymer.

[0146] Comparative Example 4:

[0147] Compared with Example 1, the difference lies in that polyacrylic acid of equal mass is used instead of polystyrene-polyacrylic acid copolymer.

[0148] Comparative Example 5:

[0149] Compared with Example 7, the difference lies in that no modified wollastonite fiber is added.

[0150] Comparative Example 6:

[0151] Compared with Example 7, the difference lies in that unmodified wollastonite fiber of equal mass is used to replace the modified wollastonite fiber.

[0152] Comparative Example 7:

[0153] Compared with Example 7, the difference lies in that the modified wollastonite fiber is the surface-modified wollastonite fiber prepared in Comparative Example 1.

[0154] Comparative Example 8

[0155] Compared with Example 7, the difference lies in that the modified wollastonite fiber is the surface-modified wollastonite fiber prepared in Comparative Example 2.

[0156] Comparative Example 9

[0157] Compared with Example 7, the difference lies in that the modified wollastonite fiber is the surface-modified wollastonite fiber prepared in Comparative Example 3.

[0158] Comparative Example 10

[0159] Compared with Example 7, the difference lies in that the modified wollastonite fiber is the surface-modified wollastonite fiber prepared in Comparative Example 4.

[0160] Performance Test

[0161] 1. Mechanical property and high-temperature resistance test:

[0162] According to GB / T50081-2019 Standard Test Method for Mechanical Properties of Ordinary Concrete, the 28-day compressive strength test was carried out on the recycled aggregate concrete prepared in Examples 7-14 and Comparative Examples 5-10. Subsequently, the test materials were placed in an environment of 400°C for high-temperature test. After cooling for 3 days, the compressive strength was tested and the strength retention rate was calculated. The number of samples in each group was three, and the average compressive strength of each group of samples was calculated. The test results are shown in Table 1.

[0163] 2. Water penetration resistance test:

[0164] According to the water penetration height method in GB / T50082-2009 Standard Test Method for Long-Term Performance and Durability of Ordinary Concrete, the water penetration resistance of the recycled aggregate concrete prepared in Examples 7-14 and Comparative Examples 5-10 was tested. The number of samples in each group was three, and the average water penetration height of the three samples was calculated. The test results are shown in Table 1.

[0165] 3. Chloride ion penetration resistance test:

[0166] According to the RCM method in GB / T50082-2009 Standard Test Method for Long-Term Performance and Durability of Ordinary Concrete, the chloride ion penetration resistance of the recycled aggregate concrete prepared in Examples 7-14 and Comparative Examples 5-10 was tested. The number of samples in each group was three, and the average chloride ion diffusion coefficient of the three samples was calculated. The test results are shown in Table 1.

[0167] 4. Crack resistance test:

[0168] According to GB / T50082-2009 Standard Test Method for Long-Term Performance and Durability of Ordinary Concrete, the early-age cracking experiment was carried out, and the crack resistance of the concrete prepared in Examples 7-14 and Comparative Examples 5-10 was tested. The number of samples in each group was three, and the average cracking area of the three samples was calculated. The test results are shown in Table 1.

[0169] Table 1 Performance test results of Examples 7-14 and Comparative Examples 5-10

[0170]

[0171] As can be seen from Table 1, combining the test results of Example 7 and Examples 11 - 12, it can be seen that as the dosage of aluminum sol in the modified wollastonite fiber increases, it helps to improve the compressive strength, impermeability and crack resistance of recycled aggregates. Combining the test results of Example 7 and Examples 13 - 14, it can be seen that as the dosage of polystyrene - polyacrylic acid copolymer in the modified wollastonite fiber increases, the impermeability and crack resistance of recycled concrete are improved.

[0172] It can also be seen from Table 1 that the strength retention rates of Examples 7 - 14 are all greater than those of Comparative Examples 5 - 10, indicating that the wollastonite modification method provided by the present invention is beneficial to improving the strength retention rate of recycled concrete at high temperatures and can improve the high - temperature resistance performance of recycled concrete.

[0173] It can also be seen from Table 1 that the test results of the compressive strength, impermeability and crack resistance of Examples 7 - 14 are all better than those of Comparative Examples 5 - 10. Among them, no wollastonite fiber was added in Comparative Example 5, unmodified wollastonite fiber was used in Comparative Example 6, the wollastonite fiber in Comparative Example 7 was not treated with aluminum silicate modification, the wollastonite fiber in Comparative Example 8 was not treated with polystyrene - polyacrylic acid copolymer modification, polystyrene was used instead of polystyrene - polyacrylic acid copolymer to modify the wollastonite fiber in Comparative Example 9, and polyacrylic acid was used instead of polystyrene - polyacrylic acid copolymer to modify the wollastonite fiber in Comparative Example 10, and the test results of compressive strength, impermeability and crack resistance all became worse. Thus, it can be seen that the wollastonite modification method provided by the present invention is beneficial to improving the compressive strength, impermeability and crack resistance of recycled concrete.

[0174] The above - mentioned is only the exemplary implementation manner of the present invention, and does not thus limit the patent scope of the present invention. All equivalent structural transformations made under the technical concept of the present invention by using the content of the specification of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A preparation method of surface-modified wollastonite fibers, characterized in that, It includes the following steps: S1. Mix wollastonite fibers and aluminum silicate sol to obtain wollastonite fibers coated with aluminum silicate sol; S2. Calcinate the wollastonite fibers coated with aluminum silicate sol to obtain wollastonite fibers modified with aluminum silicate; S3. Mix the wollastonite fibers modified with aluminum silicate and an amino-silane coupling agent to carry out a coupling reaction to obtain wollastonite fibers modified with amino groups; S4. Mix the wollastonite fibers modified with amino groups and a polystyrene-polyacrylic acid copolymer to carry out a crosslinking reaction to obtain wollastonite fibers with surface modification.

2. The preparation method of the surface-modified wollastonite fiber according to claim 1, characterized in that, Before step S1, it further includes: Mix a silicate ester, an aluminum salt, and an ethanol aqueous solution to obtain a mixed solution, and then mix the mixed solution and an acid solution to carry out a hydrolysis and polycondensation reaction to obtain aluminum silicate sol; Wherein, the molar ratio of the silicate ester to the aluminum salt is (2-3):

1.

3. The preparation method of the surface-modified wollastonite fiber according to claim 1, characterized in that, In step S1: The mass ratio of the wollastonite fibers to the aluminum silicate sol is 100:(3-6); and / or, The method of mixing the wollastonite fibers and the aluminum silicate sol includes: stirring the wollastonite fibers and the aluminum silicate sol at 60-80°C for 6-12 h.

4. The preparation method of the surface-modified wollastonite fiber according to claim 1, characterized in that, In step S2: The calcination temperature is 400-600°C; and / or, The calcination time is 2-4 h.

5. The preparation method of the surface-modified wollastonite fiber according to claim 1, characterized in that, In step S3: The amino-silane coupling agent includes 3-aminopropyltriethoxysilane; and / or, The mass ratio of the wollastonite fibers modified with aluminum silicate to the amino-silane coupling agent is 100:(1-3); and / or, The temperature of the coupling reaction is 55-65°C; and / or, The time of the coupling reaction is 5-7 h; and / or, The pH value of the coupling reaction is 4-5.

6. The preparation method of the surface-modified wollastonite fiber according to claim 1, characterized in that, In step S4: The mass ratio of the wollastonite fibers modified with amino groups to the polystyrene-polyacrylic acid copolymer is 1:(0.5-1.2); and / or, The temperature of the crosslinking reaction is 20-30°C; and / or, The time of the crosslinking reaction is 12-24 h; and / or, The pH value of the crosslinking reaction is 7-8.

7. A surface-modified wollastonite fiber, characterized in that, The wollastonite fibers with surface modification are prepared according to the preparation method of the wollastonite fibers with surface modification according to any one of claims 1-6.

8. An application of the wollastonite fibers with surface modification according to claim 7 in the preparation of recycled aggregate concrete.

9. Use of the surface-modified wollastonite fiber according to claim 8 in the preparation of recycled aggregate concrete, characterized in that, The preparation of the recycled aggregate concrete includes the following steps: Provide a cementitious material, modified wollastonite fibers, a water reducer, a suspending agent, water, fine aggregate, and recycled coarse aggregate; Mix the cementitious material and the modified wollastonite fibers and stir to obtain a rubber mixture; mix the water reducer, the suspending agent, and water and stir to obtain an admixture solution; Mix the rubber mixture, the admixture solution, the fine aggregate, and the recycled coarse aggregate and stir to obtain recycled aggregate concrete; Wherein, the modified wollastonite includes the wollastonite fibers with surface modification according to claim 7.

10. Use of the surface-modified wollastonite fiber according to claim 9 in the preparation of recycled aggregate concrete, characterized in that, The mass ratio of the gelling material, modified wollastonite fiber, water reducer, suspending agent, water, fine aggregate and recycled coarse aggregate is 100:(0.1 - 0.3):(0.8 - 1.5):(0.1 - 0.3):(40 - 60):(120 - 150):(180 - 220); and / or, The gelling material includes cement and silica fume, and the mass ratio of the cement and silica fume is (9 - 10):(1 - 1.8); and / or, The fine aggregate includes natural sand, and the particle size of the natural sand is 0.05 - 4.0 mm; and / or, The recycled coarse aggregate includes recycled crushed stone, and the particle size of the recycled crushed stone is 5 - 20 mm.